1974
DOI: 10.1111/j.1439-0329.1974.tb00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Poplar rusts in Australia with comments on potential conifer rusts

Abstract: Melampsora medusae Thüm. and M. larici‐populina Kleb. have been recorded in Australia for the first time. Their detection, spread and host range are described. M. medusae has the wider host range, but occurs mainly on Populus deltoides clones and hybrids. M. laricipopulina occurs mainly on P. nigra var. italica. Detailed descriptions are given of both rusts, and their geographic distribution listed. The possible effect of these rusts on Australian forestry is discussed, and several other rusts in Australia wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…via nursery and garden plants) are likely to be the greatest dispersers of myrtle rust, however, nectar-feeding fauna, such as bats and birds, could also act as vectors, especially in those host plants that are likely to have myrtle rust high in the crown, such as M. quinquenervia. Experience with poplar rust (Melampsora medusa)-which spread from greater-Sydney north to Queensland and south to Victoria within 14 weeks of detection (Walker et al 1974)-provide some indication of how rapidly rusts can spread with suitable hosts and climatic conditions. Experiments in situ at IP1 revealed that during the colder winter months on the Central Coast of NSW the period from inoculation to sporulation (latent period) lengthened significantly.…”
Section: Discussionmentioning
confidence: 99%
“…via nursery and garden plants) are likely to be the greatest dispersers of myrtle rust, however, nectar-feeding fauna, such as bats and birds, could also act as vectors, especially in those host plants that are likely to have myrtle rust high in the crown, such as M. quinquenervia. Experience with poplar rust (Melampsora medusa)-which spread from greater-Sydney north to Queensland and south to Victoria within 14 weeks of detection (Walker et al 1974)-provide some indication of how rapidly rusts can spread with suitable hosts and climatic conditions. Experiments in situ at IP1 revealed that during the colder winter months on the Central Coast of NSW the period from inoculation to sporulation (latent period) lengthened significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Interregional movement of pathogens and plant material can lead to new epidemics. Melampsora larici-populina Kleb., a poplar leaf rust fungus native to Eurasia, was introduced and subsequently spread on exotic poplars planted in Australia (Walker et al, 1974), New Zealand and South Africa in the 1970s, leading to the failure of intensively managed plantations of hybrid poplars . In contrast, in Quebec, this rust species has frequently been found on susceptible hybrid clones since the first report in 2001 (Innès et al, 2004), but its impact on poplar production remains low for the time being (Péri-net, unpublished results).…”
Section: Diseasesmentioning
confidence: 99%
“…Experience with previous rust incursions informed the decision that eradication was unlikely to be effective and that spread would be rapid. Poplar rust (Melampsora medusae), for example, was detected in the Sydney region in 1972 and within 14 weeks had spread north to Queensland and south to Victoria (Walker et al 1974). Antirrhinum rust (Puccinia antirrhini) was detected in a b c d e Fig.…”
Section: Discussionmentioning
confidence: 97%